Ultrasound-assisted assessment of visceral and subcutaneous adipose tissue thickness. Methodological guidelines - O. M. Drapkina; R. K. Angarsky; E. A. Rogozhkina; O. A. Maksimova; A. A. Ivanova; E. V. Zyatenkova; O. N. Dzhioeva (Кардиоваскулярная терапия и профилактика, 2023)
Methodological guidelines have been developed for inpatient internists, general practitioners, paramedics providing healthcare care in accordance with the professional standard "internist", "general practitioner". The guidelines are based on consensus papers, accumulated clinical and scientific experience. The methodology for organizing and conducting an ultrasound-assisted assessment of visceral adipose tissue is described in detail. Algorithms for diagnosing visceral obesity are presented to help the practitioner. Particular attention is paid to visceral fat assessment using ultrasound-assisted examination. These guidelines will be of interest to doctors, heads of healthcare facilities, as well as students of medical universities.